Expert and qualitative evaluation of game phases in handball - Rogulj, N.; Foretic, N.; Cavala, M. (Sport Science - International Scientific Journal of Kinesiology, 2020)
The research has been conducted with the purpose of doing expert and quantitative valorisation of the importance of four game phases in handball: position attack, position defence, transition attack and transition defence. The sample of entities involved 19 elite international handball experts and 44 matches played at the World Handball Championship for Men. We established defence phases are more important than attack phases in addition to higher efficiency and significance of transition phases compared to position phases. With regard to the research findings, we quantitatively determined the most efficient game phase combinations in handball, separately and integrally with the opposed team. Research results can contribute to the efficiency of the training process by using most useful contrasted game phase models, but also to the quality tactical preparedness and in addition to managing the match itself.